Is Anticoagulant Necessary in Patients with Coronary Artery Ectasia Presenting with Acute Coronary Syndrome? A Systematic Review of Case Reports - Pranata, Raymond; Yonas, Emir; Chintya, Veresa; Alkatiri, Amir Aziz (International Journal of Angiology, 2019)
Coronary artery ectasia is found in 3 to 8% of patient's undergoing angiography and may sometimes induce acute myocardial infarction. Some articles reported a recurrence of acute coronary syndrome (ACS) in the presence of coronary artery ectasia (CAE). Our study aims to summarize the latest evidence on whether the use of anticoagulant in addition to SAPT/DAPT (single antiplatelet/dual antiplatelet) treating ACS with CAE patients is necessary. Since the trials concerning our objectives were scarce, we pooled case reports/series. We performed a comprehensive search on case reports/series on coronary artery ectasia that presented with acute coronary syndrome published until March 2019. We collected 13 cases from 11 reports. Out of 13 patients, 5 (38.5%) took DAPT only without anticoagulant and 8 (61.5%) took anticoagulant ± DAPT. Three out of five (60%) who took DAPT only, experienced recurrences at 1st and 2nd months' follow-up. The other two (40%) was uneventful at a mean of two months' follow-up. Eight patients who took anticoagulant were uneventful for a mean of 8.4 months. Those who took anticoagulant were at lower risk of experiencing ACS recurrence (p = 0.035). Two of the patients who experienced recurrence became 6 and 12 months free after optimal anticoagulation. The author of this study proposed that anticoagulant must be considered should SAPT/DAPT failed to provide adequate protection to the recurrence of ACS, especially in CAE patients who did not have other obvious stenotic lesions. However, the evidence is weak since this study only pooled case reports/series.
Keywords: acute coronary syndrome; coronary artery ectasia; recurrence; antiplatelet; anticoagulant; antithrombotic; triple therapy